Communication and Resource Synergy for Effective Educational Administration Management: Sinergi Komunikasi dan Sumber Daya untuk Pengelolaan Administrasi Pendidikan yang Efektif - Elin Izza Maulidah; Isna Fitria Agustina; Titin Dwi Handayani; Charista Diva Vernanda; Faizzatul Lailiyah; Stevanus Dandi (International Consortium of Education and Culture Research Studies, 2025)
General Background Educational administration constitutes a fundamental foundation for managing school systems to ensure optimal operational productivity. Specific Background In Indonesia, administrative management frequently encounters severe operational challenges, including incompetent human resources within budget-constrained institutions and critical communication hurdles such as misunderstandings or unclear information flow. Knowledge Gap Although administrative theory emphasizes structured organization, planning, and supervision, empirical realities demonstrate that inefficient communication significantly increases staff and teacher workloads, resulting in task duplication and execution errors. Aims This case study research analyzes educational administration management at SMK Negeri 1 Jabon with a specific focus on communication effectiveness and resource availability. Results Findings reveal that inefficient communication triggers overlapping tasks and administrative errors, whereas the intervention of auxiliary internship personnel successfully overcomes communication barriers by preparing and distributing formal information documents. Furthermore, adequate human resources, budgets, and facilities serve as primary driving forces for successful implementation. Novelty This research specifically identifies structured internship personnel interventions as a practical mechanism to mitigate internal communication breakdowns and alleviate administrative burdens in vocational schools. Implications Educational institutions must optimize auxiliary personnel support and improve internal communication channels to safeguard staff productivity and achieve quality teaching goals. Highlights: auxiliary internship personnel successfully resolve communication hurdles through formal document preparation and distribution adequate human resources, budgets, and facilities operate as essential catalysts for administrative success deficient communication generates task duplication and administrative errors that increase staff and teacher workloads Keywords: Educational Administration, Communication Effectiveness, Resource Availability, Internship Intervention, Administrative Management